A Typology of Corruption Resistance for Public Sector Organizations - Pick, David; Issa, Theodora; Hughes, V.; Sawyer, A.; Teo, S. (Australian and New Zealand Academy of Management (ANZAM), 2012)
The aim of this paper is to enable a better understanding of corruption resistance in public sector organizations by identifying and addressing significant gaps in theory and research. To this end institutional theory is employed to propose a definition of corruption resistance and develop this definition into a typology. In the typology, four modes of corruption resistance are identified: ‘drift’, ‘laissez-faire’, ‘regulation’ and ‘alignment’. This typology is expanded using variables that have so far been identified in published research. This paper contributes by providing a theory-based definition and typology of corruption resistance which open-up opportunities for new lines of inquiry that have the potential to produce new understandings. It might also assist decision-makers and managers in public sector organizations.